Efektivitas Bimbingan Kelompok dengan Teknik Assertive Training dalam Meningkatkan Self Disclosure Siswa Kelas XI SMAN 4 Pandeglang - Rosilah Nurfitriah; Vasco Delano; Fitri Arnita (Program Studi Bimbingan dan Konseling, FKIP Universitas Pancasakti Tegal, 2025)
Student development is not only measured in academic terms but also in psychological and emotional aspects. One important aspect is Self Disclosure, the ability of students to express thoughts, feelings, and personal experiences appropriately. Initial observations at SMAN 4 Pandeglang showed that many eleventh-grade students had low levels of Self Disclosure, characterized by reluctance to express opinions, difficulty sharing personal experiences, and a tendency to withdraw. This study aims to describe the general level of students’ self disclosure, design group counseling services using Assertive Training techniques, and test their effectiveness in improving Self Disclosure. The research method used was a quasi-experiment with a nonequivalent control group design. The sample consisted of 20 students divided into an experimental group (10 students with low Self Disclosure) and a control group (10 students with moderate Self Disclosure). The research instrument was a Self Disclosure questionnaire based on Hargie’s six aspects (2011). The results showed an increase in the experimental group’s mean score from 74.3 (pretest) to 88.5 (posttest). The Wilcoxon test showed a significance value of 0.000 < 0.05, indicating that the null hypothesis was rejected. In conclusion, group counseling with Assertive Training techniques is effective in improving Self Disclosure among eleventh-grade students at SMAN 4 Pandeglang.